Child Health Problems in Indonesia - Julie Sulianti Saroso (Paediatrica Indonesiana, 1975)
Community survey and hospital data related to morbidity in children was presented. Morbidity point prevalence rate by age per 1000 population was found highest in preschool children. Acute respiratory infections, infection and inflammation of the skin and subcutaneous tissues and diarrheal disease were the most prevalent diseases among this age group. Hospital data showed that tetanus was the most serious disease. Data on the availability of health services and the utilization of these services for prevention and in case of illness as well as steps to strengthen these services was also presented.